A review on turmeric drying technologies. (2022) - Malik, Amit; Kumar, Mahesh
Abstract: Turmeric (Curcuma longa) is being used by humans since ancient times due to its amazing medicinal properties. But being a plant product and having the presence of moisture content there is always a chance of its degradation. Open sun drying has been used traditionally to overcome this problem but due to uncontrolled operating conditions, this technique has several drawbacks such as high drying time and poor product quality. Several controlled drying methods such as mechanical, microwave and solar drying have been developed to improve the overall efficiency of the drying process with quality products. In mechanical and microwave dryers, heated air and electromagnetic waves are used to dry the product. The present article gives an overview of various turmeric drying techniques available in the literature that will help novice researchers.